2014
DOI: 10.20396/conex.v12i2.2169
|View full text |Cite
|
Sign up to set email alerts
|

Composición corpora de futbolistas profesionales en función de la edad cronológica

Abstract: RESUMOEstudar a composição corporal de jogadores de futebol em relação a idade cronológica e anos de treinamento são importantes indicadores na avaliação, diagnóstico, prescrição e controle do treinamento. Objetivo: Analisar a composição corporal de jogadores profissionais de futebol em relação à idade cronológica. Métodos: A amostra foi composta por 95 jogadores profissionais que atuavam na primeira divisão do campeonato do futebol Peruano. Foram avaliadas as variáveis: Idade cronológica, anos de treinamento,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Other authors who have related CC to injuries suffered by football players have shown that the ratio of fat mass to bone mass of a body segment correlates inversely with the risk of injury [8][9][10][11][12][13]. In this sense, we can indicate that low fat-free mass (FFM) values are associated with low levels of strength, which leads to sports injuries [14]. Similarly, there is a relationship between increased BMI and low %FMG values with an increased risk of injury for young football players [15].…”
Section: Introductionmentioning
confidence: 97%
“…Other authors who have related CC to injuries suffered by football players have shown that the ratio of fat mass to bone mass of a body segment correlates inversely with the risk of injury [8][9][10][11][12][13]. In this sense, we can indicate that low fat-free mass (FFM) values are associated with low levels of strength, which leads to sports injuries [14]. Similarly, there is a relationship between increased BMI and low %FMG values with an increased risk of injury for young football players [15].…”
Section: Introductionmentioning
confidence: 97%
“…Other authors who have related BC to injuries suffered by football players have shown that the ratio of fat mass to bone mass of a body segment correlates inversely with the risk of injury [9,14]. In this sense, it can be suggested that low fat-free mass values are associated with low levels of strength, which leads to sports injuries [15]. Similarly, there is a relationship between increased BMI and low BFP values with an increased risk of injury for young football players [16].…”
Section: Introductionmentioning
confidence: 99%